Hello from MrBillDoesMath!
Answer:
a^6 + 4 a^5 + 5 a^4 - 5 a^2 - 4 a - 1
Discussion:
You may need to clean things up a bit but suppose that
S(1) = a-1
S(2) = a^2 -1
Since this is a geometric series, the geometric ratio is given by
S(2)/ S(1) = (a^2 -1)/ (a-1)
= (a+1)(a-1)/ (a-1)
= a+1
Conclusion:
S(2) = (a+1) S(1) = (a+1) (a-1)
S(3) = (a+1) S(2) = (a+1) (a+1) (a-1) = (a+1)^ (3-1) (a-1)
S(4) = (a+1) S(3) = (a+1) * (a+1)^2 (a-1) ) = (a+1)^(4-1) (a-1)
in general.....
S(n) = (a+1)^ (n-1) (a-1)
So
S(6) = (a+1)^ (6-1) (a-1)
= (a-1) (a+1) ^ 5
= a^6 + 4 a^5 + 5 a^4 - 5 a^2 - 4 a - 1
Hope I didn't screw something here!
Thank you,
MrB